Epigenetic and blood markers associated with response to electroconvulsive therapy in patients with depressive disorders - Stavrum, Anne-Kristin; Sirignano, Lea; Frid, Leila M.; Frank, Josef; Foo, Jerome Clifford; Spindola, Leticia M.; Höffler, Kira D.; Oedegaard, Ketil J.; Haavik, Jan; Rietschel, Marcella; Witt, Stephanie; Kessler, Ute; et al. (Translational Psychiatry, 2025)
Electroconvulsive therapy (ECT) is an effective antidepressant treatment. The mechanisms behind the therapeutic effect are not fully understood, and reliable biomarkers for response are needed. Epigenetic modifications, such as DNA methylation (DNAm), can reflect both genetic and environmental impacts; they may shed light on the mechanisms behind treatment effects and they have the potential to inform response prediction. We performed an epigenome-wide association study (EWAS) in peripheral blood from patients before and after ECT in a Norwegian cohort (n = 65). The methylation levels of 12 differentially methylated CpG positions (DMPs) and 18 differentially methylated regions (DMRs) were significantly associated with percent clinical response. In addition, 29 DMPs and 23 DMRs were significantly associated with remission (Montgomery and Åsberg Depression Rating Scale MADRS < 10 post treatment). Two DMRs were also significantly associated with percent response at baseline and four DMRs were significantly associated with remission at baseline (FDR < 0.05). We did not identify any longitudinal (pre-post) changes in DNAm. We further performed the first meta-analysis (n = 99) between ECT cohorts, combining this Norwegian cohort and a German ECT cohort (n = 34). Seven of the DMRs found to be associated with response in the meta-analyses were previously identified in the Norwegian or the German cohort (FDR < 0.05). Methylation risk scores (MS) calculated using DMPs associated with ECT in the Norwegian cohort showed promising association with response to ECT in the German cohort (p = 0.06). Finally, we found increased neutrophil to lymphocyte ratios, calculated from estimated cell proportions, to be associated with remission (p < 0.003) in the Norwegian cohort.
Gesehen am 17.02.2026